Control system of labour safety measures in the higher educational institution - O. G. Feoktistova; T. G. Feoktistova (Научный вестник МГТУ ГА, 2016)
The article examines a system of labour safety measures control. With the introduction of the integrated system of management the competitive ability of production and organization, the effectiveness of its activity rise, and sinnergicheskiy effect is also reached and the savings of all forms of resources are ensured. Objectives and methods of control system of labour safety measures in enterprises are developed, including in the educational institutions.